11(2+8x)-10(10-11x)=912

Simple and best practice solution for 11(2+8x)-10(10-11x)=912 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 11(2+8x)-10(10-11x)=912 equation:


Simplifying
11(2 + 8x) + -10(10 + -11x) = 912
(2 * 11 + 8x * 11) + -10(10 + -11x) = 912
(22 + 88x) + -10(10 + -11x) = 912
22 + 88x + (10 * -10 + -11x * -10) = 912
22 + 88x + (-100 + 110x) = 912

Reorder the terms:
22 + -100 + 88x + 110x = 912

Combine like terms: 22 + -100 = -78
-78 + 88x + 110x = 912

Combine like terms: 88x + 110x = 198x
-78 + 198x = 912

Solving
-78 + 198x = 912

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '78' to each side of the equation.
-78 + 78 + 198x = 912 + 78

Combine like terms: -78 + 78 = 0
0 + 198x = 912 + 78
198x = 912 + 78

Combine like terms: 912 + 78 = 990
198x = 990

Divide each side by '198'.
x = 5

Simplifying
x = 5

See similar equations:

| -2(x-18)=(-x/2+3)(-3) | | 12=4n-10 | | x^3=216 | | -5=-x+3 | | 6x+2+3x+17=10 | | 3n+6n=3-9 | | .6a-.75b=c | | 7(-2x+6)=126 | | 5a^2+20a+3=0 | | -3q+4=q | | 3(3x+4)+3(3x+4)=18x+30 | | 7x+4+4x+9=10x+3 | | 3(x+7)-3(x+2)=36 | | 6y^2+9y=11y-4 | | 4v^2-28v+49=0 | | 3(x+7)-3(x+2)=-36 | | 6+8(x-9)=9-3(x-9) | | z-5=7z-9-z | | x-6=7x | | x=5my-7b | | 8x+3-7x=11 | | 16w^2+27=0 | | 36x^2+12x+64=0 | | 12=8n-1 | | 3w-11w=48 | | 6=4x-9y | | 5(1.2k+6)=7.1+34.4 | | -7(6x+1)=-133 | | (9x^2)-252x+330=0 | | x-4x+3=-30 | | -3(3n-8)=30 | | p=-3*4+1 |

Equations solver categories